Scandium(III) Triflate Catalyzed Reductive Etherification of Carbonyl Compounds with Alcohols Using 1,1,3,3-Tetramethyldisiloxane as the Reducing Agent - Nobuta, Tomoya; Yamagiwa, Noriyuki; Mineno, Tomoko (Synlett, 2025)
In this study, we present a straightforward protocol for the reductive etherification of carbonyl compounds with alcohols using a catalytic amount of scandium(III) triflate [Sc(OTf)3] and 1,1,3,3-tetramethyldisiloxane to produce nonsymmetrical ethers. The reaction proceeds under mild room-temperature conditions and accommodates a broad range of substrates, including α,β-unsaturated aldehydes, yielding the desired products in good to excellent yields. Notably, the catalyst loading of Sc(OTf)3 could be reduced to 0.1 mol%.
Keywords: reduction; etherification; carbonyl compounds; ethers; scandium triflate catalysis; hydrosilanes